Public Debt – Energy Consumption Nexus - Raouf, Engy (International Journal of Energy Economics and Policy, 2022)
As energy demand has risen and continues to rise, a growing body of research examines the impact of a variety of factors on energy use, including economic development, price changes, and international trade. The public debt–energy consumption nexus, on the other hand, has received little attention. This study looks at the effect of government debt on both renewable and nonrenewable energy usage in 17 OECD countries from 1980 to 2020. Using the Generalized Least Square (GLS) panel data estimation method and Panel Quantile Regression (PQR), this paper finds that public debt has a favorable influence on the utilization of renewable energy and a detrimental influence on the use of non-renewable energy. It can be noticed from the PQR that all variables have more favorable impacts on renewable and nonrenewable energy usage at higher quantiles.